Starborn : how the stars made us (and who we would be without them) - Trotta, Roberto (Basic Books, Hachette Book Group, 2023)
"Here's what it is about: For tens of thousands of years, the stars were our constant companions. In the glow of today's artificial lighting, when even professional astronomers study the universe by staring at screens rather than through eyepieces, we have forgotten this intimacy with the cosmos. Roberto Trotta is here to remind us: one of our species' most enduring and (literally) universal relationships has been with the night sky itself. In Starborn, cosmologist Trotta shows how stargazing has shaped the entire course of human civilization. The rhythm of our ancestors' lives revolved around the stars, from their cycles of agriculture to their patterns of birth. Our origin myths made the Sun into a life-giving creator and the Milky Way a gateway for departed souls. The motion of celestial bodies sustained the illusion that the Earth was at the center of the cosmos-until looking at them more closely sparked the Scientific Revolution. Across the ages stars have served as clocks, maps, compasses, muses, and gods, defining both our laws of reality and our dreams of the sublime. How radically different would humanity be, Trotta also asks, if our ancestors had looked up to the night sky and seen... nothing? In lyrical yet evidence-grounded meditations he imagines a world without stars, a dramatic alternate history in which we wouldn't understand gravity, where we couldn't navigate or have much sense of time, and where our sense of the profound--of art and of the divine--was altered beyond recognition. Revealing the hidden connections between astronomy and the story of civilization, Starborn summons us to the marvelous sight that awaits us on a dark, clear night--to lose ourselves in the immeasurable vastness above"--